A Mathematical Model of COVID-19 with Double Doses of Vaccination and Quarantine - Lutfia Husna Khoirunnisa; Stevanus Budi Waluya (Unnes Journal of Mathematics, 2022)
Covid-19 (coronavirus disease 2019) is a disease caused by a virus called SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), and began to appear at the end of 2019. One of the ways to prevent the spread of covid-19 from spreading is to provide double-dose vaccination and quarantine for individuals who can transmit covid-19 (infectious). Through this research, a mathematical model was formed for the case of the spread of covid-19 by considering the existence of double-dose vaccination, and quarantine were given to infectious. In the model formed, we get a basic reproduction number R0, and two equilibrium points, namely the disease-free equilibrium point (E0 ) that will be locally asymptotically stable when R_0<1, and the endemic equilibrium point (E* ) that will be locally asymptotically stable when R0>1. Furthermore, in the numerical simulation carried out, it is known that double doses of vaccine and quarantine can decrease the transmission of covid-19.